An experimental and simulation-based study on the effect of carbonyl iron, heavyweight aggregate powders, and carbon fibres on the electromagnetic shielding properties of cement-based composites. (27th December 2021) - Wanasinghe, Dimuthu; Aslani, Farhad; Ma, Guowei
Highlights: CIP and HP powders did not have a significant effect on mechanical properties. Electrical conductivity gradually reduced with the particle content. CIP and 12 mm CF composite produced a shielding efficiency of 51.30 dB. 3 mm and 12 mm CF composite generated an EMI SE of 50 dB. Limitations in the simulation software led to mismatch with experimental results. Abstract: Research into electromagnetic interference (EMI) shielding has been growing over the last couple of decades due to shortcomings of existing methods and increased demand. Therefore, the construction industry has also been interested in fabricating a cement-based composite that could be used for EMI shielding without the use of additional cladding material. This research is focused on fabricating a cement-based composite that could be used for EMI shielding with the addition of carbonyl iron powder, heavyweight aggregate powder, and carbon fibres. Several mix designs were carried out by varying the additives used to find the content that would produce optimal properties. All the mixes were tested for their mechanical, electrical conductivity, and EMI shielding properties. EMI shielding tests were carried out per ASTM D4935 – 18 standard within 30 MHz to 1.5 GHz frequency range. The mix consisting of 20% carbonyl iron powder in combination with 0.7% of 12 mm CF produced an EMI shielding of 51.30 dB, which was the best result obtained for any mix in this research. An additional simulation was carried out using CST Studio software to see the theoretical level of shielding produced by these mixes. The simulation results showed near identical results to that of the experimental with smaller variation at specific frequencies.